PENYULUHAN KEPADA MASYARAKAT DI WILAYAH RW 04 KELURAHAN KLENDER JAKARTA TIMUR TERKAIT PENCEGAHAN KOMPLIKASI DIABETES MELITUS - Rahmat Widiyanto; Gilang Al Qarana (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Diabetes Mellitus (DM) is often referred to as the silent killer because sometimes the symptoms of this disease are not realized by the sufferer. This results in the treatment often being carried out by sufferers quite late. In fact, it is not uncommon for sufferers to only treat DM after complications occur. Adequate knowledge and awareness from the community are needed to avoid DM (for non-sufferers) and minimize DM complications (for sufferers). This is the aim of the Community Service (PkM) activities of the IKIFA lecturer team in RW 03, Klender Village, East Jakarta. The PkM activity took place on Thursday, July 11, 2024, with a theme related to Counseling regarding the Prevention of DM Complications, which was attended by 57 respondents. The counseling method using Power Points is used in this PkM activity. During the discussion process between the lecturer team and respondents, it appeared that respondents were quite active in discussing and asking questions. So, it can be concluded that the PkM activities were successful in accordance with the initial objectives to be achieved.